Nonparametric identification and stimation of nonadditive hedonic Models - James Joseph Heckman; Rosa Liliana Matzkin; Lars Nesheim (Institute for the Study of Labor (IZA), 2009)
This paper studies the identification and estimation of preferences and technologies in equilibrium hedonic models. In it, we identify nonparametric structural relationships with nonadditive heterogeneity. We determine what features of hedonic models can be identified from equilibrium observations in a single market under weak assumptions about the available information. We then consider use of additional information about structural functions and heterogeneity distributions. Separability conditions facilitate identification of consumer marginal utility and firm marginal product functions. We also consider how identification is facilitated using multimarket data.
urn:nbn:de:101:1-2009090135
Keywords: C14; D41; D58; 330; Hedonic models; hedonic equilibrium; nonadditive models; identification; non-parametric estimation; Nutzentheorie; Unvollkommene Information; Offenbarte Präferenzen; Hedonischer Preis; Nichtparametrisches Verfahren